FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BURUK PADA BALITA DI KELURAHAN SEI.LAKAM BARAT KECAMATAN KARIMUN KABUPATEN KARIMUN - Nilma, Nilma; Mona, Silvia (Universitas Batam, 2019)
Malnutrition is a severe level of malnutrition due to low consumption of energy and protein from daily food that occurs for quite a long time. Poor nutrition can affect children's growth and development, as well as children's intelligence. At a more severe level, when combined with poor care, poor sanitation, and the emergence of other diseases, malnutrition can lead to death. Data from Karimun district health office, there are 0.9% cases of malnutrition, 0.4% in Karimun sub-district and 1% in West Sei.Lakam sub-district in 2017. The purpose of this study is to determine the factors that influence malnutrition status in toddlers. This study used an analytical survey with a cross sectional approach. This research was conducted in February-July in Sei.Lakam Barat Subdistrict, Karimun Subdistrict, with a population of all mothers who have children aged 0-59 months totaling 869 people. The sampling technique is quota sampling with a total sample of 90 people. The measuring instrument used was a questionnaire which was analyzed univariately and bivariately using the chi-square statistical test at Î± 0.05. The results showed that there was a relationship between maternal knowledge and nutritional status of children under five (p = 0.047). There is no relationship between maternal education and nutritional status of children under five (p = 0.581). There is a relationship between the economy and the nutritional status of toodlers (p = 0.037). It is recommended that there be continuous health education activities on toddler nutrition for mothers of toddlers so that mothers can provide nutritious food for toddlers